The influence of soot nanoparticles on the micro/macro-scale behaviour of coalescing filters - Mead-Hunter, R.; Bredin, Arne; King, Andrew; Larcher, Alfons; Becker, Thomas; Mullins, Benjamin (Elsevier, 2012)
This work examines the filtration of soot-in-oil colloid aerosols,utilising both whole filter testing andsingle fibre force measurements.It was found that the presence of soot increases the equilibriumpressure drop of coal escing filters subject to discontinuous operation;such as those used in enginecrank case ventilation. We have found that this pressure drop increase may be explained by the increase in effective oil viscosity caused by the presence of soot, but that this may not delay the onset of drainage,as the soot was found not to increase droplet displacement forces. Soot accumulation in the filter has been observed, on the same order of magnitude as could be expected due to physical deposition mechanisms